2017
DOI: 10.1186/s12864-017-3705-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral immune priming with Bacillus thuringiensis induces a shift in the gene expression of Tribolium castaneum larvae

Abstract: BackgroundThe phenomenon of immune priming, i.e. enhanced protection following a secondary exposure to a pathogen, has now been demonstrated in a wide range of invertebrate species. Despite accumulating phenotypic evidence, knowledge of its mechanistic underpinnings is currently very limited. Here we used the system of the red flour beetle, Tribolium castaneum and the insect pathogen Bacillus thuringiensis (Bt) to further our molecular understanding of the oral immune priming phenomenon. We addressed how inges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 76 publications
6
59
2
Order By: Relevance
“…Interestingly a new and unexpected regulatory process has been described recently for invertebrates. Two recent studies reveal that the primary and the secondary immune responses, developed against the same parasite, involve different immune effector systems resulting in a transcriptional shift . This transcriptional shift was highlighted in mollusk and insect and involved a substantial set of differentially expressed transcripts that were over or under‐represented exclusively following the secondary immune challenge.…”
Section: Toward a Unifying Model For Innate Immune Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly a new and unexpected regulatory process has been described recently for invertebrates. Two recent studies reveal that the primary and the secondary immune responses, developed against the same parasite, involve different immune effector systems resulting in a transcriptional shift . This transcriptional shift was highlighted in mollusk and insect and involved a substantial set of differentially expressed transcripts that were over or under‐represented exclusively following the secondary immune challenge.…”
Section: Toward a Unifying Model For Innate Immune Memorymentioning
confidence: 99%
“…This transcriptional shift was highlighted in mollusk and insect and involved a substantial set of differentially expressed transcripts that were over or under‐represented exclusively following the secondary immune challenge. In Biomphalaria snails, this immune shift will changed the immune cellular encapsulation response toward a humoral immune response while in the coleopteran Tribolium, immune shift results in an enhanced pleiotropic immune capabilities …”
Section: Toward a Unifying Model For Innate Immune Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of associations between priming and different immune components was surprising, given prior work with other insects showing that priming is beneficial because it induces more efficient immune responses (Barribeau, Schmid-Hempel, & Sadd, 2016, but also see Greenwood et al, 2017; and that components of innate and external immunity (quinone secretion outside the body; Joop et al, 2014) trade off (Cotter et al, 2013).…”
Section: Shirasumentioning
confidence: 99%
“…Overall, antibacterial activity did not explain the observed variation in primimg response, highlighting that the association between innate immune responses and survival after priming may not be straightforward in wild populations. This is surprising since previous studies with Tribolium beetles found that priming with B. thuringiensis increases expression of a large set of immune related genes (Greenwood et al 2017), correlating strongly with survival after reinfection (Milutinović et al 2013). We note that whereas our hemolymph antibacterial activity assay may reflect the impact of several immune pathways such as antimicrobial peptides, it is possible that other aspects of innate immunity such as cellular defence (e.g.…”
Section: Discussionmentioning
confidence: 77%